Analyzing Student Engagement through LMS Log Data in an Applied Statistics Course - Ishaq Ishaq; Salwa Rufaida; Syamsidar Saleng (Journal of Educational Sciences, 2026)
This study analyzes student engagement in an Applied Statistics course by integrating Learning Management System (LMS) activity logs, cognitive assessments, and student reflections. The primary objective is to investigate how behavioral engagement within a digital learning environment influences academic achievement. Employing a mixed-method approach descriptive qualitative supported by basic quantitative analysis this study collected data from five students through SPADA Unismuh LMS logs, pre-and post-tests, and semi-structured interviews. Quantitative findings show high engagement levels, with material access ranging from 47 to 51 times and forum participation between 7 and 8 times. These behaviors corresponded to substantial learning gains, with an average score increase exceeding 48%. Pearson correlation analysis revealed strong and significant relationships between LMS activity and academic improvement (r = 0.88 for material access; r = 0.85 for discussion participation). Qualitative insights indicated that multimedia-based materials (animations, infographics) and interactive forums enhanced comprehension of abstract concepts and fostered independent learning. By combining behavioral, cognitive, and experiential data, this study proposes a holistic framework for evaluating student engagement in digital learning. The findings contribute to the literature on learning analytics and offer practical guidance for enhancing engagement in small-class online learning environments.